2019
DOI: 10.2514/1.j057876
|View full text |Cite
|
Sign up to set email alerts
|

Active Flow Control on Vertical Tail Models

Abstract: Active flow control (AFC) subscale experiments were conducted at the Lucas Wind Tunnel of the California Institute of Technology. Tests were performed on a generic vertical tail model at low speeds. Fluidic oscillators were used at the trailing edge of the main element (vertical stabilizer) to redirect the flow over the rudder and delay or prevent flow separation. Side force increases in excess of 50% were achieved with a 2% momentum coefficient (C μ) input. The results indicated that a collective C μ of about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Fluidic actuators placed at a tail of an aircraft were simulated using unsteady RANS and validated by means of experimental results by Shmilovich et al [44]. More recently, Andino et al [45] tested fluidic actuators in a generic tail at low speeds and demonstrated that a modest increase in the momentum coefficient can result in important increments of the side force. Whalen et al [46] presented wind-tunnel test results of the AFC of the vertical tail of a Boeing 757 equipped with sweeping jet actuators; a significant increase in the side force at a maximum rudder deflection of 30 • was observed.…”
Section: Active Control Of Separationmentioning
confidence: 99%
“…Fluidic actuators placed at a tail of an aircraft were simulated using unsteady RANS and validated by means of experimental results by Shmilovich et al [44]. More recently, Andino et al [45] tested fluidic actuators in a generic tail at low speeds and demonstrated that a modest increase in the momentum coefficient can result in important increments of the side force. Whalen et al [46] presented wind-tunnel test results of the AFC of the vertical tail of a Boeing 757 equipped with sweeping jet actuators; a significant increase in the side force at a maximum rudder deflection of 30 • was observed.…”
Section: Active Control Of Separationmentioning
confidence: 99%
“…Fluidic actuators placed at a tail of an aircraft were simulated using unsteady RANS and validated by means experimental results by Shmilovich et al [44]. More recently, Andino et al [45] tested fluidic actuators in a generic tail at low speeds and demonstrated that a modest increase of the momentum coefficient can result in important increments of the side force. Whalen et al [46] presented wind-tunnel test results of the AFC of the vertical tail of a Boeing 757 equipped with sweeping jet actuators; significant increase in the side force at maximum rudder deflection of 30 • was observed.…”
Section: Active Control Of Separationmentioning
confidence: 99%
“…One of the most prominent research areas is focused on using fluidic oscillators for active flow control. These devices have been shown to prevent flow separation over a highly deflected surface, thereby significantly increasing the aerodynamic performance of aircraft [11][12][13]. It is hypothesized that fluidic oscillators are more efficient than steady jets and require less mass flow, because the jets' sweeping motion provides greater lateral impact, thereby allowing for increased jet spacing and fewer jets needed.…”
Section: Figurementioning
confidence: 99%